International Migration and the (Un)happiness Push: Evidence from Polish Longitudinal Data. Issue 4 (December 2021) - Brzozowski, Jan; Coniglio, Nicola
This article analyzes the impact of (un)happiness on the international migration decision. It uses a rich longitudinal household-level database, the Polish Social Diagnosis, to identify migration intentions, as well as subsequent actual migration, allowing us to overcome the issue of reverse causality present in previous studies of the nexus between happiness and migration. In addition, we assess the role of individual and household levels of happiness on migration behaviors and find that unhappy individuals from unhappy households are significantly more likely to declare their intentions to migrate abroad. In terms of actual migration, however, the unhappiness push significantly affects the odds of international migration only for selected subgroups, such as women and employed individuals. For other individuals, the unhappiness-induced migration plans remain mostly unrealized. Our article shows that push and pull factors, including happiness, might exert heterogenous effects on migration intentions and actual realizations. As a consequence, migration scholars should be careful when drawing conclusions on the determinants of actual migration behaviors by looking at determinants of migration intentions.